Research on long-term outcomes of meniscectomy - G. K. Kamushadze (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. The menisci of the knee joint (medial and lateral) play an important role in shock absorption and stabilization. Their tears are among the most common injuries, especially in athletes and older individuals. The main treatment methods are partial or total meniscectomy and reconstruction (meniscal repair). The relevance of this issue lies in the increasing number of surgeries and the potential long-term complications, including accelerated osteoarthritis (OA). Objective. To systematize and analyze existing data on the long-term outcomes of meniscectomy, identify factors influencing these outcomes (patient age, anterior cruciate ligament status, and level of physical activity), and propose practical recommendations for optimizing treatment and rehabilitation. Materials and Methods. A literature review was conducted, including randomized trials, meta-analyses, and clinical observations, focusing on the evaluation of outcomes following meniscectomy and meniscal repair. Data were considered on the incidence and severity of osteoarthritis, functional outcomes (WOMET, Lysholm scale, IKDC, OARSI), and reinjury rates in different age groups. Special attention was paid to meniscal preservation strategies and combined ACL reconstruction in the context of longterm results. Results. Partial or total meniscectomy increases the load on the articular cartilage, thereby contributing to OA progression. Several randomized trials have shown a faster increase in radiographic and clinical signs of OA in the meniscectomy group compared to placebo surgery. Younger patients (under 22) have a higher risk of recurrent tears and poorer functional outcomes due to greater physical stress. Meanwhile, no statistically significant differences in reconstruction failure rates were noted in patients over 40. Combined ACL reconstruction and meniscal repair yield more favorable long-term results, though the literature is contradictory. Some studies indicate a lower rate of recurrent tears with simultaneous ACL reconstruction and meniscal suturing, potentially linked to improved stability and additional stimulation of healing (release of growth factors and stem cells during tunnel drilling). Preserving the meniscus through reconstruction (repair) is associated with better functional outcomes and a lower risk of OA compared to meniscectomy. Resection (especially total) more often leads to reduced scores on the IKDC, WOMET, and Lysholm scales, as well as increased pain syndrome. Conclusions. Complete or partial meniscectomy significantly increases the risk of osteoarthritis and decreases joint functionality. Preference should be given to reconstructive procedures (meniscal repair), especially in the red and red-white zones of the meniscus, which have better blood supply and regenerative potential. Patients under 22 carry a higher risk of recurrent tears, necessitating more aggressive repair strategies and rigorous rehabilitation oversight. Combined ACL reconstruction and meniscal repair can improve stability and reduce reinjury risk, although further research is needed to confirm this effect. An individualized approach to meniscal tears—considering patient age, activity level, and tear type—as well as the use of biological agents and comprehensive rehabilitation (exercise, weight management, regular check-ups) promotes more favorable long-term outcomes and helps prevent osteoarthritis.